Understanding the oxidation mechanism of Fe (1 0 0) in supercritical CO2: A ReaxFF molecular dynamics simulation. (September 2022) - Yang, Yu; Zhou, Junjie; Yu, Yinsheng
Abstract: In this study, to understand the oxidation mechanism of transmission pipeline surface (Fe) in supercritical CO2 (SCO2 ), the microstructure of Fe/SCO2 system was established, and molecular dynamics (MD) simulations were performed using reactive force field (ReaxFF), the oxidation mechanism was revealed at nanoscale. The results indicated that the initial oxidation of Fe was induced by the absorption of SCO2 molecules near the iron surface. The dynamic evolution of atom behavior and charge transfer were clarified and observed. It was found that the surface iron atoms lose more electrons than the inner iron atoms, the delamination of the simulated system was demonstrated by us, and the carbon deposition in the desquamation area was also observed. It is demonstrated that a low area density can contribute to the occurrence of oxidation reaction. The oxidation reaction rate is rapid at initial stage, and it decreases with the increase of oxidation reaction time. Graphical Abstract: Modeling of the Fe/SCO2 system. ga1 Highlights: The dynamic revolution of atom behavior and charge transfer during oxidation were clarified and explored. The delamination of the system was demonstrated, and carbon deposition in the desquamation area was also observed. The oxidation mechanism of Fe surface in SCO2 was revealed by ReaxFF molecular dynamics simulations.